Artificial intelligence techniques in philosophy of truth and untruth and religion / Nelly Astuti Hasibuan … [et al.] - Hasibuan, Nelly Astuti; Harmayani, Harmayani; Ginting, Guidio Leonarde; Saputra, Imam; Utomo, Dito Putro (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Artificial intelligence technology is growing rapidly in line with the development of human thought, where many human activities and activities have now been replaced by computers. The development of artificial intelligence technology has caused many changes in the pattern of human life, human civilization, interaction and communication between humans and other changes. These changes have positive and negative impacts. One of the positive impacts is that the development of technology allows computers to help human work with better results. Such as the application of artificial intelligence techniques in determining the value of truth and untruth or determining the fatwa for the law of an event that is still the same or has doubts in it. By applying artificial intelligence techniques such as fuzzy logic and probability or uncertainty techniques, the results will be more objective.